2002
DOI: 10.1002/neu.10166
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate models of drug abuse

Abstract: Susceptibility to drug addiction depends on genetic and environmental factors and their complex interactions. Studies with mammalian models have identified molecular targets, neurochemical systems, and brain regions that mediate some of the addictive properties of abused drugs. Yet, our understanding of how the primary effects of drugs lead to addiction remains incomplete. Recently, researchers have turned to the invertebrate model systems Drosophila melanogaster and Caenorhabditis elegans to dissect the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
141
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 146 publications
(159 reference statements)
2
141
0
2
Order By: Relevance
“…[64]). The present results have gone on to demonstrate that studies of reward are well within the scope of invertebrate psychostimulant studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[64]). The present results have gone on to demonstrate that studies of reward are well within the scope of invertebrate psychostimulant studies.…”
Section: Discussionmentioning
confidence: 99%
“…[64]), naturalistic interpretations of crayfish drug reward may derive from evolutionary and ecological considerations. For example, it will be important to study the mechanisms by which amphetamine infusions are able to be ~two-fold more effective than cocaine infusions for crayfish CPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not nearly as complex in its behavioral repertoire as higher mammals, Drosophila is an excellent model organism that blends genetic accessibility and behavioral complexity. Drosophila has been successfully used in dissecting genetic components of behavioral paradigms including associative learning and memory (DeZazzo and Tully, 1995), substance abuse (Wolf, 1999;Wolf and Heberlein, 2003), circadian behavior (Wang and Sehgal, 2002), and recently sleep (Hendricks et al, 2001;Shaw et al, 2002). It is also very suitable for the study of gene interactions and epistasis.…”
Section: Introductionmentioning
confidence: 99%
“…26 The links between dopaminergic pathways and addictive behavior have been examined in C. elegans. 31,32 In a C. elegans model of ethanol intoxication, activation of a BK potassium channel, SLO-1, has been shown to have a central role in the acute neurobehavioral effects of this substance. 27 A recent study has revealed the important role that CRH-1, the C. elegans homolog of CREB, has on the worm's foraging rate through regulation of tph-1 (tryptophan hydroxylase), which is necessary for serotonin production.…”
Section: Caenorhabditis Elegansmentioning
confidence: 99%